Simple Additive Weighting: Determination of The Local Government Officials Tanggamus Region - Satria Abadi; Miswan Gumanti (bit-Tech, 2024)
This study aims to determine regional officials in the Tanggamus region using a decision support system based on the Simple Additive Weighting (SAW) method. In the government official environment, determining regional officials is crucial as they are government employees who hold important positions at both regional and provincial levels. The issue of determining regional officials in the Tanggamus area is significant due to various problems such as the behavior of officials, absenteeism, lack of socialization in society, and more. This study employs the SAW method, which involves variables like educational level, behavior of officials, and rank. This system is designed to aid in decision-making for selecting responsible regional officials who are accountable for their duties. The findings indicate that the SAW method is effective in evaluating alternatives based on predefined criteria. Officials appointed in an area must possess honesty in performing their duties and comply with established regulations. This system allows for a more transparent and accurate process in determining regional officials. The results of this study are expected to provide a decision support information system for regional officials in the Tanggamus region, ensuring that selected officials have the necessary qualifications and integrity to fulfill their roles.